The Influence of Scientific and Technical Progress on the Transformation of Power and Society Resources - D. G. Popov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to resources of the power and society, their main types and limits on their use. The authors consider the priority and the principles of use of different types resources depending on a stage of scientific and technical progress, a type of society, the level of development of civil society and public control institutes, the character of a political regime. It is noted that in the conditions of transition to post-information (communication) society the main value is gained by non-material resources of the power and society. Special attention is paid to communication and technological resources of the power and society. The authors investigate also different approaches to understanding of network resources, it is noted that they are not only the means of Internet communication and they are not the attribute of exclusively modern society.